The Prognostic Value of β-catenin Expression in Endometrial Cancer - Il Ji, Yong (International Journal of Innovative Research in Medical Science, 2017)
Objective: To investigate the prognostic value of β-catenin expression in endometrial cancer. Methods: Immunohistochemistry was used to evaluate samples from 27 early stage and 39 advanced stage endometrial cancers. Smears were examined for the expression of β-catenin protein in the cell membrane, cytoplasm, and nucleus. The staining patterns were then evaluated for their correlation with several prognostic factors, including 5-year survival. Results: Decreased cell membrane β-catenin expression was significantly associated with advanced stage (stage III–IV), high grade (grade 3), deep (>50%) myoinvasion, and positive lymph node status (P < 0.05). Negative membrane staining for β-catenin was associated with a lower 5-year survival rate, compared to that for positive staining (51.7% vs. 86.6%, respectively; P < 0.05). Conclusions: Loss of membrane β-catenin expression is a strong and independent predictor of unfavorable outcomes in patients with endometrial carcinoma.